The tick-borne diseases research programme at ILRAD - Dolan, T.T. (International Laboratory for Research on Animal Diseases, 1995)
The Tick-Borne Diseases Programme at the International Laboratory for Research on Animal Disease (ILRAD) has as its own major objective the improvement of the control of tick-borne diseases by immunological means. The focus of its research has been a novel vaccine for Theileria parva, the cause of East Coast fever (ECF) in 11 countries in eastern, central and southern Africa. Conventional control of tick-borne diseases in this region is by strict tick control using regular application of acaricides in dips or sprays. ILRAD's approach to the development of a new vaccine against T. parva has been through exploring the protective immune in cattle. This work has identified CD8+ T-cell responses directed against parasite antigens on the surface of infected lymphocytes as the major response. An important research objective is to complete the development of these technologies as reliable and robust diagnostic and epidemiological tools for the complex of tick-borne diseases. The long-term objective is the development of antigen-based vaccines for the major tick-borne diseases that can be designed to protect cattle in particular challenge environments. These vaccines will be applied where the tick-borne disease epidemiology has been defined so that the most appropriated control strategy is used.